2017
DOI: 10.3892/ijmm.2017.3117
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 promotes the proliferation and odontoblastic differentiation of human dental pulp cells under high glucose conditions

Abstract: Insulin-like growth factor-1 (IGF-1) promotes human dental pulp stem cell proliferation and osteogenic differentiation. However, the effects of IGF-1 on the proliferation, apoptosis and odontoblastic differentiation (mineralization) of dental pulp cells (DPCs) under high glucose (GLU) conditions remain unclear. In this study, isolated primary human DPCs were treated with various concentrations of high GLU. Cell proliferation and apoptosis were determined by Cell Counting Kit-8 and Annexin V-FITC/PI assays, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…A heat map of the key transcripts for the osteo/dentinogenic differentiation process is shown in Figure 6E. These genes were consistent with those related to osteo/dentinogenic differentiation that were identified in previous reports [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Rna Sequence Analysissupporting
confidence: 87%
“…A heat map of the key transcripts for the osteo/dentinogenic differentiation process is shown in Figure 6E. These genes were consistent with those related to osteo/dentinogenic differentiation that were identified in previous reports [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Rna Sequence Analysissupporting
confidence: 87%
“…They did not specify the sample that they used to acquire the DPSCs. Shunro Miyashita et al [ 9 ] and Yan et al [ 10 ] on the other hand used both first premolar and third molar for their studies. There is no inflamed pulp tissue used in any of the studies, even though Alongi et al [ 11 ] reported that it is an appropriate source for isolation of DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, IGF-1 significantly reversed the effects of high GLU. IGF-1 restored ALP activity and promoted odontoblastic differentiation by increasing the expression levels of mineralization-related proteins as mentioned above [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [ 163 ] further revealed the role of the IGF-1/IGF-1R/hsa-let-7c axis in regulating the committed differentiation of SCAPs. Yan et al [ 164 ] reported that IGF-1 rescued the adverse effects of high glucose concentration on DPSCs and protected against apoptosis. Regarding periodontal ligament regeneration, IGF-1 was shown to enhance the survival of PDLSCs[ 165 ].…”
Section: Cell Function Optimization Strategiesmentioning
confidence: 99%